T cell mediated immunity after combination therapy with intralesional PV-10 and blockade of the PD-1/PD-L1 pathway in a murine melanoma model. - Hao Liu (PLoS ONE, 2018)
Intralesional (IL) injection of Rose Bengal (PV-10) induces regression of injected and uninjected lesions in several murine tumor models. In this study, we investigated the anti-tumor response of combining IL PV-10 with blockade of the PD-1 / PD-L1 pathway and the role of immune cell populations in eliciting this response. To investigate the role of T cell subsets in mediating an immune response, B16 or M05 melanoma-bearing mice received combination therapy as well as CD8+, CD4+, or CD25+ depleting antibodies. Tumor growth was measured. T cells were collected from spleens or tumors, and phenotype, activation markers, and reactivity were measured. Splenocytes from mice treated with combination therapy had increased OVA antigen-specific CD8+ T cells in M05-tumor-bearing mice. Depletion of CD4+ T cells or regulatory T cells (Tregs) in combination with IL PV-10 and anti-PD-1 antibody treatment resulted in an enhanced anti-tumor effect. Treatment with CD8+ depleting antibody abrogated anti-tumor immunity. These results support a clinical study for the safety and anti-tumor immune responses with combination therapy of IL PV-10 and PD-1/PD-L1 blockade.